Serviço Técnico de Biblioteca e Documentação - Freitas, Izamar da Silva; Manzatti, Ana Claudia Martins Grieger; Matsumoto, Claudio Hideo; Oliveira, Ana Paula Rimoli de; Nakamura, Denise Haruyo; Munhoz, Ivone Rosa de Lima; Sedlacek, Luis Claudio; Anderlini, Luzia; Benez, Maria Claudia de Castro (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação Izamar da Silva Freitas Ana Claudia Martins Grieger Manzatti Claudio Hideo Matsumoto